2002
DOI: 10.1081/jdi-120002659
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Interdialytic Weight Gain With Nutritional Parameters and Mortality Risk in Hemodialysis Patients

Abstract: High interdialytic weight gain (IDWG) is considered as an indicator of noncompliance but could also be interpreted as an index of appetite. This study was designed to investigate the relationship IDWG with malnutrition and mortality risk in hemodialysis (HD) patients through a follow-up of 24 months. We divided HD patients into two groups according to their IDWG as Group I (IDWG < 3% of dry weight/day) (27 patients; age 46.8 +/- 21.1 years; HD duration: 28.3 +/- 39.5 months) and Group II (IDWG > or = 3% of dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 22 publications
5
50
1
4
Order By: Relevance
“…5,8,9,12,21 In addition, although retrospective analyses suggested that a large percentage of IDWG was associated with increased risk of mortality, 6,7 recent investigations noted an increased percentage of IDWG to be associated with improved nutritional parameters and improved mortality. 10,[22][23][24] Thus, some postulated that the lack of relationship between moderate hypertension and outcomes may be caused by the benefit of additional volume and caloric intake, which can increase BP parameters. However, in our investigation, the impact of day-to-day volume intake on BP was modest, suggesting that intake volume may not have a significant role in the lack of association between moderate hypertension and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,8,9,12,21 In addition, although retrospective analyses suggested that a large percentage of IDWG was associated with increased risk of mortality, 6,7 recent investigations noted an increased percentage of IDWG to be associated with improved nutritional parameters and improved mortality. 10,[22][23][24] Thus, some postulated that the lack of relationship between moderate hypertension and outcomes may be caused by the benefit of additional volume and caloric intake, which can increase BP parameters. However, in our investigation, the impact of day-to-day volume intake on BP was modest, suggesting that intake volume may not have a significant role in the lack of association between moderate hypertension and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the available epidemiological evidence suggested that moderate hypertension likely was well tolerated in hemodialysis patients, 5,9,11,12,21 the relationship between BP and outcomes is confounded by such factors as day-to-day variations in fluid intake that are associated with nutritional status and subsequent clinical outcomes. 10,[21][22][23][24][25] Thus, defining the independent relationship between IDWG and BP has important clinical implications.…”
Section: Index Wordsmentioning
confidence: 99%
“…(3) IDWG as a marker of better nutrition: Several studies have found that IDWG was associated with better nutritional status [51,52,53,54,55,56,57], suggesting a role of greater appetite and higher food and fluid intake.…”
Section: Interdialytic Weight Gain: Reported Causes and Consequencesmentioning
confidence: 99%
“…Estes achados são discordantes em relação à maioria dos trabalhos disponíveis na literatura, nos quais o maior GPID foi encontrado em pacientes com melhor estado nutricional. 8,18 Apesar de não termos avaliado a ingestão alimentar dos pacientes estudados, podemos supor que no nosso grupo de pacientes, o %GPID esteve mais associado à ingestão de sódio e líquidos em si do que ao consumo energético-proteico total. Além disso, é comum encontrarmos preferência por alimentos líquidos ou semilíquidos em pacientes com desnutrição.…”
Section: Discussionunclassified